Successful treatment of immune checkpoint inhibitor-related periaortitis - Elias D. Bührer; Ian L. Alberts; Lisa Christ; Berna C. Özdemir (Swiss Medical Weekly, 2024)
We report a 64-year-old patient with melanoma receiving ipilimumab and nivolumab therapy who presented with a periaortic soft tissue mass around the abdominal aorta on restaging fluorodeoxyglucose positron emission tomography/computed tomography imaging. Clinical, laboratory, and radiologic findings resulted in a diagnosis of immune checkpoint inhibitor-related periaortitis. Periaortitis is a rare disease presenting with fibro-inflammatory tissue around the aorta and may lead to serious complications. Immune checkpoint inhibitors were discontinued, and the patient was treated with glucocorticoids, leading to a complete resolution of the periaortitis. To our knowledge, this is only the third reported case of immune checkpoint inhibitor-related periaortitis.